A Critical Review of Virtual Communities and Social Media in Framing the Case of Persecution against Gus Fuad Plered - Muhammad Ya’la ‘Ali Sadad (Lembaga Yasin AlSys, 2026)
Religious thought diversity in Indonesia frequently generates tensions, as illustrated by the 2023 persecution of KH Muhamad Fuad Riyadi (Gus Fuad Plered) in Bantul, Yogyakarta, by conservative groups such as Front Jihad Islam (FJI). This study analyzes the digital framing of this incident on YouTube by addressing three questions: (1) how media narratives and comments frame the incident; (2) how Mohammed Arkoun’s deconstruction problematizes conservative responses; and (3) what implications arise for religious pluralism. Employing qualitative framing analysis based on Entman (1993) and deconstruction following Arkoun (1984, 2002), the study thematically codes data from two viral videos (with more than 822,000 views) and 1,000 netizen comments across four dimensions: problem definition, causal diagnosis, moral judgment, and treatment recommendation. Purposive sampling is used to capture peak discourse, and triangulation strengthens the validity of the analysis. The findings show that the conflict is framed as intra-Muslim friction over amar ma'ruf nahi munkar, with Gus Fuad’s critique of habib figures reframed as symbolic blasphemy; the causes are linked to epistemological divides concerning religious authority, intensified by platform algorithms; moral judgments predominantly condemn violence as violating Islamic adab; and proposed solutions emphasize dialogue and digital literacy. Through Arkoun’s lens, the study reveals dogmatic rigidity that obstructs contextual ijtihad and constrains pluralistic engagement. The study concludes that social media functions as a polarizing arena in post-FPI religious conflicts while simultaneously providing a space for counter-framing that supports pluralism, thereby advancing the literature on digital religious communication and underscoring the need for Islamic organizations to promote multidisciplinary da'wah and media education to foster tolerance within Indonesia’s diverse ummah.